Highly sensitive detection of NT-proBNP by molecular motor - Jie Zhang; Yao-Gen Shu (Genes and Diseases, 2017)
FoF1-ATPase is an active rotary motor, and generates three-ATP for each rotation. At saturated substrate concentration, the motor can achieve about 103 r.p.m, which means one motor can generate about 105 ATP molecules during 30 min. Here, we constituted a novel nanodevice with a molecular rotary motor and a “battery”, FoF1-ATPase and chromatophore, and presented a novel method of sandwich type rotary biosensor based on ε subunit with one target-to-one motor, in which one target corresponds 105 ATP molecules as detection signals during 30 min. The target such as NT-proBNP detection demonstrated that this novel nanodevice has potential to be developed into an ultrasensitive biosensor to detect low expressed targets.